The Effect of Shelter-In-Place on Orthopedic Trauma Volumes in Italy During the COVID-19 Pandemic - Andreozzi, Valerio; Marzilli, Fabio; Muselli, Mario; Previ, Leonardo; Cantagalli, Matteo Romano; Princi, Giorgio; Guzzini, Matteo; Ferretti, Andrea (Acta Biomedica Atenei Parmensis, 2021)
Background: The COVID-19 outbreak heavily attacked Italy, putting a strain for an extended time on the National healthcare system.  Hospitals fastly rearranged the activity to cope with the crisis. This retrospective comparative study intended to investigate the impact of the lockdown imposed in Italy, in two different periods, during the COVID-19 outbreak on acute orthopedic trauma, in order to identify significant issues for improvement and future preparation. Materials and methods: We obtained data on total trauma access to a single University hospital DEA (Department of Emergency and Acceptance) in Rome during two periods of the COVID-19 pandemic lockdown in Italy: from March 9th, 2020 to May 4th, 2020(Phase 1), from May 10th, 2020 to June 30th, 2020(Phase 2) and then comparing them with the analogous period in 2019. We recorded demographic data; the characteristics of the lesion, including the anatomical area, fracture, sprain, dislocation, contusion, laceration, whether the lesion site was exposed or closed, where the trauma occurred and polytrauma. We also reported the waiting time in the emergency room and the mode of transport. Result: The study sample was composed of 1655 patients, 894 (54%) males and 761 (46%) females. The overall number of admissions in 2019 (pre-COVID-19 period) was 995; then it was 204 during Phase 1 and increased again to 456 during Phase 2. The average age of the Phase 1 group was 51.9 ± 24.8 years, signiﬁcantly higher than that of the 2019 group (41.4 ± 25.7) and Phase 2 group (42.2 ± 22.5 years) (p=65 years) were the most commonly involved in the Phase 1 group, while in the pre-COVID-19 period and in Phase 2 they were middle-aged adults (15-44 years) (p